Dua Muka Ancaman: - Alam, Teduh Gentar (Jurnal ICMES, 2024)
Foreign terrorist fighters (FTF) is a security threat that now becomes the attention of many countries, especially after the rapid expansion of ISIS in Syrian conflict. Terrorism has been chosen as a violent tactic by FTF when they are part of their organization to express and achieve their political aspirations and agendas. This study uses the human security approach to explain the FTF phenomenon. The concept of terrorism and FTF is also explained to complete the analysis. This research uses the qualitative method by conducting in-depth interviews with several ex-FTF sources. This study finds that when FTF become a human security threat to people outside their group, at the same time FTF also perceive a threat to themselves, their thoughts, and their community. Because of that, counterterrorism efforts in Indonesia need to use human security approach and mitigate human security threats as perceived by both FTF and people at risk becoming FTF.